TINDAK PIDANA KEKERASAN FISIK TERHADAP ISTRI YANG TIDAK MENGGANGGU AKTIVITAS KORBAN - Santo Reynaldo; Vience Ratna Multiwijaya (Fakultas Hukum Universitas Trisakti, 2022)
In the matter addressed in Decision Number 3/Pid.Sus/2020/PN.Lss, a woman was physically abused in the home without the victim's participation. The issue in this case is how judges decide whether to convict someone for using physical force against their wife while she is a household member in accordance with Article 44 Jo. Article 5 Law No. 23 of 2004 regarding the abolition of domestic violence (Case Study of Decision Number 3/Pid.Sus/2020/Pn.Lss), and why judges do not impose conditional sentences on those who commit such crimes. The research approach is normative legal research, which is descriptive and analytical. It uses primary data collected through interviews and secondary data gleaned through literature studies. The data is processed qualitatively by making logical deductions. The study's findings, analysis, and conclusion show that the judge, when weighing the evidence, accords little weight to the theories of balance and ratio decidendi. The judge's conditional ruling is the result of the judge's belief that whoever commits the offense must bear responsibility and that the defendant has been deterred by the judge's decision to sentence the defendant to six months in prison.